Latin American Reality of English Teacher Education in Universities: A Systematic Literature Review - Romero-Argueta, Jesús (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This systematic literature review investigates the current state of English teacher education in Latin American universities, highlighting key challenges and opportunities in the preparation of competent educators. Drawing on peer-reviewed literature sourced from academic databases such as Google Scholar and Semantic Scholar, the study synthesizes findings from recent publications in both English and Spanish. The analysis reveals persistent curriculum deficiencies, notably the disproportionate emphasis on theoretical knowledge at the expense of practical training, limited integration of information and communication technologies (ICT), and inadequate incorporation of cultural identity. Additionally, neoliberal educational policies are found to hinder pedagogical innovation by prioritizing accreditation metrics over meaningful instructional reform. Despite these challenges, emerging approaches such as interactive didactics demonstrate promise, with evidence indicating a 4% improvement in teaching efficiency. The review advocates for curriculum models that balance linguistic competence, hands-on teaching experience, and cultural responsiveness, while also addressing digital inequities and systemic policy barriers. Future research should assess the long-term efficacy of innovative pedagogical strategies and develop context-sensitive models to strengthen English teacher education across diverse Latin American contexts.